Gene delivery to neural stem cells using minicircles and plasmids without CpG motifs - Reis, Mónica Sofia Correia dos, 1986- (2011)
Tese de mestrado. Biologia (Biologia Celular e Biotecnologia). Universidade de Lisboa, Faculdade de Ciências, 2011